2018
DOI: 10.1021/acs.inorgchem.8b01519
|View full text |Cite
|
Sign up to set email alerts
|

An EPR Investigation of Binding Environments by N-Donor Chelating Exchange Resins for Cu Extraction from Aqueous Media

Abstract: Chelating exchange resins (CERs) are now widely used for metal extraction in aqueous acidic media. Many of these CERs contain surface N-donor ligands, such as di(2-picolylamine) (BPA) and picolylamine (PA), which are highly selective for Cu(II) uptake. Two such widely used resins are Dowex M4195 and CuWRAM. Surprisingly, very little is known about the Cu(II) binding environments on the exchange resins, particularly at variable concentrations and pH's, and therefore we used EPR spectroscopy to investigate this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…These resins display a wide range of selectivity values towards transition metals, which depend on the different stabilities of metal complexes at the required pH conditions 2 . Typically, chelating exchange resins facilitate increased adsorption rates, efficiencies, and surface areas when compared to ion exchange resins 24 , thus, chelating resin treatment is one of the most effective and attractive methods due to the simplicity of design and ease of operation 25 .…”
Section: Introductionmentioning
confidence: 99%
“…These resins display a wide range of selectivity values towards transition metals, which depend on the different stabilities of metal complexes at the required pH conditions 2 . Typically, chelating exchange resins facilitate increased adsorption rates, efficiencies, and surface areas when compared to ion exchange resins 24 , thus, chelating resin treatment is one of the most effective and attractive methods due to the simplicity of design and ease of operation 25 .…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that 90% of the nickel was stripped from the resin with 2 bed volumes of 20 g L -1 H 2 SO 4 while only 35% copper was stripped, suggesting that a split elution could be carried out to selectively recover both metals. Spencer et al [18] evaluated the complexation mechanisms and elution of copper using the resin Dowex M4195 and free ligands 2-picolylamine. Regarding copper desorption, the authors concluded that typically, the adsorbed copper ions are released by washing with concentrated acid (1.0 −2.0 M H 2 SO 4 ) which protonate the nitrogen sites.…”
Section: Introductionmentioning
confidence: 99%
“…In many instances, it provides great insights into structural and electronic arrangements otherwise unapproachable in research ranging from fundamental solid-state physics to medicine and biophysics. Moreover, these studies are very important for the assessment of magnetic exchange interactions in the respective polynuclear and even in one-dimensional (1D), 2D, or 3D magnetic networks where the mononuclear TM complexes are used as building blocks. In practice, from the analysis of ESR and ENDOR spectra, the tensors of the hyperfine (HF) and quadrupole (Q) interactions can be determined and, using specific models, the spin density distribution can be inferred. An essential prerequisite for that is a well-resolved HF and Q structure of the spectra, which is rarely observed in concentrated solids due do the broadening effect of the dipole–dipole interaction. To eliminate this effect, paramagnetic complexes can be diluted in a nonmagnetic medium, in the simplest case in a suitable solvent.…”
mentioning
confidence: 99%